2009
DOI: 10.1111/j.1365-2648.2009.04961.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of gerontologically informed nursing assessment and referral interventions for older persons attending the emergency department: systematic review

Abstract: Title. Effectiveness of gerontologically informed nursing assessment and referral interventions for older persons attending the emergency department: systematic review. Aim. This paper is a report of a literature review conducted to analyse data from published studies reporting nursing interventions targeted at older attendees of emergency departments (EDs), and to provide a critical appraisal of the evidence concerning their effectiveness. Background. Attendance at hospital EDs by older persons presents oppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(60 citation statements)
references
References 33 publications
0
60
0
Order By: Relevance
“…Another review of effectiveness of gerontologically informed nursing assessment and referral interventions for older people in the emergency department reported mixed results for patient and health systems outcomes. Here, too, the authors stressed that testing of complex interventions in RCTs was inherently problematic [52]. …”
Section: Discussionmentioning
confidence: 99%
“…Another review of effectiveness of gerontologically informed nursing assessment and referral interventions for older people in the emergency department reported mixed results for patient and health systems outcomes. Here, too, the authors stressed that testing of complex interventions in RCTs was inherently problematic [52]. …”
Section: Discussionmentioning
confidence: 99%
“…As a first step, screening tools could serve as “triggers” to identify the need for further geriatric assessment. Also, literature suggests that screening in the ED improves efficiency of geriatric interventions [30, 3234]. Screening in ED could help in bed allocation for patients requiring hospitalisation, assigning the most vulnerable to geriatric evaluation and management units, where patient outcomes are better [35].…”
Section: Discussionmentioning
confidence: 99%
“…those factors that may influence emergency department utilisation. Systematic reviews of clinical emergency department-based interventions (Althaus et al, 2011;Fealy et al, 2009;McCusker and Verdon, 2006) have summarized the results of eight randomized controlled trials conducted in Canada (Gagnon et al, 1999;Lang et al, 2006;McCusker et al, 2003), United States (Mion et al, 2003;Shumway et al, 2008;Spillane et al, 1997), Australia (Caplan et al, 2004) and Sweden (Hansagi et al, 2008). Only one trial reported a significant impact on both secondary outcomes and revisits (Shumway et al, 2008).…”
Section: Introductionmentioning
confidence: 97%